(3ELGRGJ GdQhGjI hGdeUWdMs - (3GdWgQGfj, BZG HRQc, eMSf Hf Ydj Hf eMeO QVG, J (B1389(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3GdMeO ddg Ydi LRjd EaVGdg hLdjd fhGdg(B... (3hHYO ajbhd(B... (3YHO Gddg Hf UGdM(B...s
(3BNQgG (B:s
(3hQSGdI GdaQb hQSGdI GdefWb hTQMgG hTQM GdHGH GdMGOj(B... (3hcJH gPg GdCMQa HjOg GdaGfjI GdLGfjI GdabjQ SdjeGf(B...s
(3JHUQI GdeDda (B:s
(3Ch(B: (3eMeO eMSfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B5(3, (B288s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdMOjK hGdeUWdMs